Obsolescence Risk Assessment Process Best Practice - Romero Rojo, Francisco Javier; Roy, Rajkumar; Kelly, S. (Institute of Physics (IOP), 2013)
A component becomes obsolete when it is no longer available from the original manufacturer to the original specification. In long-lifecycle projects, obsolescence has become a major problem as it prevents the maintenance of the system. This is the reason why obsolescence management is now an essential part of the product support activities in sectors such as defence, aerospace, nuclear and railway; where systems need to be supported for several decades. The obsolescence risk assessment for the Bill of Materials is a paramount activity in order to manage obsolescence proactively and cost-effectively. This is the reason why it was necessary to undertake a benchmarking study to develop best practice in this process. A total of 22 obsolescence experts from 13 different organisations/projects from across UK and USA have participated in this study. Their current processes and experience have been taken into account in the development of the best practice process for obsolescence risk assessment. The key factors that have to be analysed in the risk assessment process for each component in the Bill of Materials are: number of manufacturers, years to end of life, stock available, consumption rate and operational impact criticality. For the very high risk components, a more detailed analysis is required to inform the decisions regarding the most suitable mitigation strategies. On the contrary, for the low risk components, a fully proactive approach is neither appropriate nor cost effective. Therefore, it is advised for these components that obsolescence issues are dealt with reactively. This process has been validated using case studies with several experts from industry and is currently being implemented by the UK Ministry of Defence as technical guidance within the JSP 886 Volume 7 Part 8.13 standards.